CFD of drag reduction II - Pey, Yin Yin. (2009)
In the aerospace industry, there is a continuous search for new methods to reduce drag. Drag reduction is important as it can translate to better fuel consumption and hence savings. This report will look into the possibility of drag reduction with the use of riblets. The idea of using riblets to reduce drag was inspired by sharks which have riblets‐like skin that has successfully aided them in achieving great speeds in water. In this study, triangular riblets will be modeled and analyzed computationally for any drag reduction effects. Two types of turbulence modeling will be used. These include the Reynolds averaged Navier Stokes (RANS) equations as well as Large Eddy Simulation (LES). Results from these two methods will be compared against each other as well as against results from a Direct Numerical Simulation (DNS) study done by Choi, Moin and Kim. Variables that will be analyzed to check for drag reduction effects include velocity, wall shear stress and vorticity. The variation of these variables due to the presence of the riblets will be discussed and any signs of drag reduction will be accounted for.